Experiences of advanced foreign developed countries in taxation of natural resources in Uzbekistan - Zokhidov Ismatzhan Yunuszhan Ogli (Genius Journals, 2023)
In this article, having studied the experience of advanced foreign countries in the taxation of natural resources in our country, it is necessary to ensure the necessary level of collection of taxes and other obligatory payments, carry out tax administration of taxpayers and radically improve Particular attention is paid to the provision of service and technical services based on mutual cooperation in the execution of tax obligations. Taxation of entrepreneurs, according to the experience of taxation of natural resources in advanced foreign countries, is a complex and difficult area that requires careful consideration and improvement. Taxation of entrepreneurs is a complex issue that requires in-depth consideration and improvement. By addressing issues related to tax treatment, transparency, tax administration and tax incentives, a more supportive and enabling environment for entrepreneurs in natural resources, investment, economic growth and sustainable development of the sector can be created
Keywords: resource tax; land use tax; tax; budget policy